"Agamemnon", "Medea" and "Trachiniae": Bloody portrait of three wives. Heroines of Greek mythology V - Esteban Santos, Alicia (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2015)
Based on tragedies of Aeschylus, Sophocles and Euripides (Agamemnon, Trachiniae and Medea respectively), we are going to confront the fi gures of Clytemnestra, Deianeira and Medea. Among them there are important analogies: all three are abandoned wives, replaced by a younger woman, and suffer jealousy and humiliation for it. All three are victims of serious injustice from their husband and suffered an immense pain because of him. Consequently, they do not remain passive, and with their action they cause the most damage to their respective husbands, being executors of horrible death. But there are also great oppositions among them, leading to the conclusion that Sophocles’ Deianeira has been shaped in antithesis to Aeschylus’ Clytemnestra and probably also to Euripides’ Medea. That is supported by the many characteristic features of Euripides (not only from Medea but also from other tragedies) that are found in Trachiniae.